2023
DOI: 10.1021/acscatal.3c01430
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the CO2 Reduction Mechanism of a Highly Active Organometallic Manganese Electrocatalyst: Direct Observation of a Hydride Intermediate and Its Implications

Abstract: A detailed mechanistic study of the electrochemical CO 2 reduction catalyzed by the fac-[Mn I (CO) 3 (bis-Me NHC)MeCN] + complex (1-MeCN + ) is reported herein by combining in situ FTIR spectroelectrochemistry (SEC), synthesis and characterization of catalytic intermediates, and DFT calculations. Under low proton concentrations, 1-MeCN + efficiently catalyzes CO 2 electroreduction with long catalyst durability and selectivity toward CO (ca. 100%). The [Mn -I (CO) 3 (bis-Me NHC)] − anion (1 − ) and the tetracar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 71 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…Interestingly, the potential ramping experiment done with the TPACo complex revealed that the dimeric hydride-carbonyl species dominated the mass spectra at potentials negative to −2 V, substantiating that this HER pathway becomes dominant at highly negative potentials (Figures b and Figure S26). Nevertheless, detecting cobalt hydride intermediate by EC-ESI-MS is remarkable as the direct detection and full characterization of hydride intermediates during the electrocatalytic reactions is rarely reported …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the potential ramping experiment done with the TPACo complex revealed that the dimeric hydride-carbonyl species dominated the mass spectra at potentials negative to −2 V, substantiating that this HER pathway becomes dominant at highly negative potentials (Figures b and Figure S26). Nevertheless, detecting cobalt hydride intermediate by EC-ESI-MS is remarkable as the direct detection and full characterization of hydride intermediates during the electrocatalytic reactions is rarely reported …”
Section: Discussionmentioning
confidence: 99%
“…Homogeneous electrocatalytic CO 2 reduction is being extensively explored to achieve reaction selectivity and serves as a mechanistic model for improved large-scale CO 2 electroreduction processes. Numerous molecular catalysts, based on the transition metal complexes, have been proposed for CO 2 reduction, generally exhibiting good product selectivity. , However, they often display mediocre electrocatalytic performance, possibly due to the poisoning or degradation of the catalyst or undesirable side reactions. ,, The in-depth investigation of the electrolytic CO 2 reduction reaction mechanism is thus imperative for developing efficient and robust molecular catalysts. Although several remarkable mechanistic studies have been reported, the fate of the catalysts during the electrocatalytic CO 2 reduction with a molecular-level insight remains under-investigated. This is primarily attributed to the limited availability of suitable analytical tools.…”
Section: Introductionmentioning
confidence: 99%
“…7 Soon thereafter, Royo and Lloret disclosed the extraordinary activity and selectivity of a Mn-based catalyst bearing a bidentate methylene-bridged bis-imidazolylidene ligand toward the electroreduction of CO 2 to CO, 8 and unveiled the factors that govern its reactivity and selectivity. 9 This Mn(I)-bisNHC complex was also found to be active in the reductive Nformylation and N-methylation of secondary amines using either CO 2 or formic acid as C 1 building blocks, showing remarkable selectivity to the N-methylated products. 10 Luca and co-workers showed that pincer Mn(I) complexes were particularly effective in the electrocatalytic reduction of CO 2 , 11 and performed detailed mechanistic studies.…”
Section: ■ Introductionmentioning
confidence: 96%
“…The cumulative emission of CO 2 is raising environmental concerns for its role in global warming, and consequently CO 2 reduction is an urgent global issue. In the face of these serious environmental problems, the capture of CO 2 has become a hot issue in recent years. However, apart from CO 2 capture and storage, research has started into the utilization of CO 2 for the synthesis of valuable chemicals and materials. Because CO 2 is a cheap, abundant, and nontoxic C 1 feedstock, it can be converted into various carbon resources such as alcohols, acids, esters, and hydrocarbons. This approach has 2-fold advantages, namely, CO 2 reduction in the atmosphere as well as reduction in the use of unrenewable fossil fuels for synthesis of these compounds. Therefore, transforming CO 2 into valuable chemicals may provide a solution to not only environmental problems caused by the emission of CO 2 but also the anticipated depletion of fossil resources.…”
Section: Introductionmentioning
confidence: 99%